VALUATION OF DOMESTIC GOVERNMENT BONDS AT THE SECURITIES MARKET - Syniavska Л.; Hrytsyna О.; Rubai О. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
The article analyses the state and problems of such important segment of the stock market as bond market, which is a powerful source of debt financing of the investment demands of issuers and the whole economy. The aim of the work is to study the dynamics and structure of the domestic market of government and corporate bonds, their profitability and risk, as well as opportunities and prospects of its development. The authors analyze the dynamics of placing of DGB (domestic government bonds) at the primary market in Ukraine, as well as the dynamics of the volume of money attracted to the State budget of Ukraine by the turnover term, and also the dynamics of profitability of domestic government bonds during the analysed period. Considering the basic indices, the researchers analyze current conditions of the bond market, its structure, positive and negative tendencies of functioning, factors that stipulate the dynamics of its conjuncture. The article substantiates the necessity of the further detailed study and analysis of the quantitative and qualitative parameters of government bonds turnover. It is confirmed that during the previous year the largest number of tenders by financial instruments was registered by the operators of the organized capital markets particularly of the domestic government bonds. The high profitability of DGB is highlighted that allows to recover inflation losses and get some profit. Reasons of the increased interest of foreign investors in domestic government bond of Ukraine are distinguished. The work points on the role of military bonds in the conditions of martial law and marks that the money of military bonds attracted from the state budget is used for the trouble-free providing of state financial needs, including social and defensive ones, in the conditions of the unbalanced budget. The negative consequences of money printing for the economy are outlined, and the necessity of macro-financial assistance provided by other countries is highlighted. The research stresses on the possibility to sell military bonds from the brief-case of NBU, the aim of which is to increase the rates of hryvnia assets. The authors of the article determine position of the different groups of participants of the domestic bond market, as well as their role and importance for the effective functioning of the debt sector of the stock market. The key components of development of the domestic bond market are defined.